Empirical Study on the Importance of Information Technology Security Audits of Nigeria’s Commercial Banks’ Emerging Technologies - Adebisi , Adeolu Abiodun; Adebisi , Akin; Amusan , Lere; Adesemowo , Kayode (Journal of Islamic, Social, Economics and Development, 2024)
In Nigeria today, modern information technologies have revolutionized Nigerian commercial banks and the financial sector by swiftly embracing cutting-edge technology like artificial intelligence, the Internet of Things (IoT), blockchain, and cloud computing. Although sophisticated and emerging technologies provide several advantages, they also bring forth new and intricate security weaknesses that entail inherent risks. This study investigates the methodical process of examining the information technology security audits of emerging technologies in commercial banking institutions in Nigeria. This work used the systematic literature review (SLR) as the methodology. The pertinent documents were collected and meticulously inspected, including vital data on the importance of information technology security audits in the Nigerian commercial banking sector. This article emphasizes the importance of information technology security audits in reducing these risks and protecting Nigerian commercial banks. The objective of this work is to improve the implementation of strong cybersecurity measures in commercial banks in Nigeria. This will be achieved by evaluating the existing level of integration of emerging technologies, identifying any weaknesses, and developing a detailed approach for performing information technology security audits. The findings indicate that the lack of advancement in the banking industry may be ascribed to deficiencies in internal control systems, poor information technology governance, and inadequate audits of the emerging technologies used by Nigerian commercial banks.